Konflik Sosial dalam Drama Roppongi Class Karya Koji Tokuo: Pendekatan Sosiologi Sastra Marxis - Ilmiah, Aisahtul; Suryawati, Cicilia Tantri; Andarwati, Titien Wahyu (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
The drama entitled Roppongi Class narrates the story of a young man with strong idealistic principles, Arata Miyabe, who becomes entangled in a social conflict with Ryuga, the son of the owner of Nagaya Holdings. Nagaya Holdings is a corporation wielding significant influence in the culinary business sector. This study aims to describe the depiction of social conflict, the causes of the conflict, the strategies employed by the protagonist to overcome it, as well as the impacts of the conflict as portrayed in Koji Tokuo’s Roppongi Class. This research employed a qualitative method applying a descriptive-analytical approach. The findings reveal representations of vertical social conflicts encompassing ideology, upper class, lower class, state-class relations, alienation in the workplace, and oppressive class structures. The causes of social conflict stem from oppression, social injustice, and disputes. The protagonist’s strategies for addressing the conflicts include competition, compromise, diagnosis, implementation, recognition, and agreement. The impacts of the social conflict are categorized into two forms: negative and positive. The negative impacts include loss of educational and employment rights, violence, and criminal punishment. Conversely, the positive impacts comprise improving social and economic status, strengthening organizatinal structures, building credibility, enhancing sense of justice, and acknowledging past mistake